Animal Models for the Analysis of Immune Responses to Leishmaniasis. (2nd February 2015) - Sacks, David L.; Melby, Peter C.
Abstract: This unit focuses on the murine model of cutaneous leishmaniasis and models of visceral leishmaniasis in mice and hamsters. Each basic protocol describes the methods used to inoculate parasites and to evaluate infections with regard to lesion progression and visceralization, and quantification of parasite load. © 2015 by John Wiley & Sons, Inc.